2011
DOI: 10.1002/adv.20217
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of nanosilica‐filled polypropylene in the molten state: Effect of particle size

Abstract: ABSTRACT:Composites of polypropylene (PP) with nontreated nanosilica at different particle sizes are prepared, and their viscoelastic properties are studied by dynamic strain-and frequency-sweep experiments. It is clear that incorporation of nanoparticles in a polymer matrix due to the huge specific surface area enhances both moduli so that the storage modulus is intensified more than loss modulus. The specific surface area of a particles increases as a particle size decreases, leading to a stronger tendency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…As observed by other authors,9, 10, 14, 21 the behavior of loss modulus is similar to that of storage modulus, but with a maximum near a critical strain in the G ″‐curve. Aranguren et al21 observed a maximum in loss modulus for nanocomposites of PDMS and untreated silica and they assumed this overshoot to be related to energy dissipation produced by the breakdown of silica aggregates.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…As observed by other authors,9, 10, 14, 21 the behavior of loss modulus is similar to that of storage modulus, but with a maximum near a critical strain in the G ″‐curve. Aranguren et al21 observed a maximum in loss modulus for nanocomposites of PDMS and untreated silica and they assumed this overshoot to be related to energy dissipation produced by the breakdown of silica aggregates.…”
Section: Resultssupporting
confidence: 85%
“…The effects of nanoparticles on the different viscoelastic properties of nanocomposites have been investigated so that the various changes in mechanical behavior of polymer composite could be observed. Several authors investigated that particle size is an effective parameter in viscoelastic properties of composite polymer melts 4–9. For example, Jianga et al7 studied the composites of acrylonitrile–butadiene–styrene (ABS) reinforced with micron and nano‐sized precipitated calcium carbonate particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rahim [3], the viscoelastic properties of nanocomposites ABS / SiO 2 polymer blends with ABS / PA6 / SiO 2 were examined. They have reported that increasing the percentage of polymer chains and reduce the size of nanoparticles increases the absorption of nanoparticles, increasing entanglement chains and create a three-dimensional network nanopaticles.…”
Section: Introductionmentioning
confidence: 99%